Seismic fragility analysis of RC frames with masonry infills - Hossameldeen Mohamed (2018)
Given the evidence provided by past earthquakes and experimental tests carried out since the mid-1950s, the contribution of the infill wall on the global response of the RC structures cannot be ignored. Therefore, the seismic vulnerability of this type of buildings needs to be assessed by considering the effect of the infill wall to determine their level of safety and, therefore, to identify their possible strengthening needs. This paper addresses the seismic fragility assessment of several reinforced concrete (RC) frames with different infill panel configurations and number of storeys. The selected structures involve fully infilled and partially infilled RC frames, as well as RC frames with an open ground floor, with four and eight storeys, whose behaviour was compared to that of the corresponding bare frames. The behaviour of the infill panel was simulated by a single strut model with properties that were calibrated using experimental data. Each structure was analysed using nonlinear dynamic analysis considering fifty real ground motion records that were scaled to several intensities. Structural performance was measured using maximum interstorey drifts over the height of the structure and fragility curves were then computed based on the demand distributions for several limit states. The fragility curves that were obtained show distinctive evolutions reflecting the different behaviour of the selected structures due to their infill configurations